A kinetics study of ligand substitution reaction on dinuclear platinum complexes: Stochastic versus deterministic approach1. Issue 1 (9th October 2018) - Iioka, Tatsuya; Takahashi, Satoshi; Yoshida, Yuichiro; Matsumura, Yoshihiro; Hiraoka, Shuichi; Sato, Hirofumi
Abstract : The kinetics on a basic ligand substitution reaction on dinuclear platinum complexes [Pt(PEt3 )2 PhPt(PEt3 )2 ] 2+ and [Pt(PEt3 )2 PhCOPhPt(PEt3 )2 ] 2+, with the ligands pyridine and 3‐chloropyridine, is studied. This is a fundamental step in a self‐assembly, and the time evolution has been observed with a new experimental technique, QASAP (quantitative analysis of self‐assembly process), which is recently developed by Hiraoka's group. As a result of numerical calculations based on master equation, we succeed in specifying the reaction rate constants with a simple reaction model. In addition, the time evolutions of all the intermediate components produced and consumed in chemical reaction are revealed, including those unobserved in the experiments. The convergence behavior of the existence ratios of specific chemical species calculated with the stochastic algorithm method is compared with those obtained from deterministic formalism based on rate equations, revealing a clear dependence on the number of constituent molecules. © 2018 Wiley Periodicals, Inc. Abstract : A ligand exchange reaction between dinuclear Pt(II) complexes with pyridine and 3‐chloropyridine ligands was studied based on the stochastic simulation algorithm. The time evolutions of all the intermediate components produced and consumed in the chemical reaction were revealed, including those unobserved in the experiments. Numerical tests have also shown a clear relation between the residual sum of squares from the results of the stochastic algorithm and the rate equation versus the numbers of molecular species..